Effect of process optimization on laser additive manufacturing of Inconel 718 alloy based on finite element analysis: Thermal and structural evaluation. (July 2023) - Meng, Guiru; Zhang, Jingdong; Zhu, Lida; Lan, Qing; Jiang, Zongze
Highlights: The dynamic simulations of the temperature and stress fields are realized. Stress distributions at multi-paths and different stress components are studied. The end ablation and core cracking in cladding layers can be well explained. Selecting small laser power and large scanning speed can reduce residual stress. The simulation error is controlled within 21 % by comparing the experiment. Abstract: In this study, a three-dimensional transient thermo-elastic-plastic model with sequential thermal-force coupled is established based on an improved temperature field model, which can realize dynamic simulations of the temperature and stress fields in laser additive manufacturing of Inconel 718 alloy under different process parameters and scanning strategies. The results show that the Von-Mises stress inside cladding layers is high and reaches the peak at the end of the clad or the connection with the substrate, and well explain the end ablation and core cracking in cladding layers. On the premise of ensuring the quality of cladding parts, a relatively small laser power and a large scanning speed should be selected as possible, and a reasonable scanning strategy can effectively avoid excessive stress concentration in cladding layers with the maximum stress reduced by about 50 MPa. The tensile limit of cladding parts can reach 902.41 MPa under the a-scanning strategy as found by tensile experiments, and the surface residual stress measured by X-ray diffraction technology varies from 186 MPa to 272 MPa. By comparing with experiment, the simulation error is controlled within 21 %, indicating that this research can provide reasonable theoretical guidance for the process optimization of the actual processing.